FACTORS INFLUENCING CAREER CHOICE AMONG NURSING STUDENTS - Kuzņecova, Jeļena; Šverina, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Choosing a career is a complex and multi-factorial decision-making process that is based on several personal, situational and organizational factors. The purpose of this study is a literature review to determine factors influencing career choice among nursing students. The literature review displays that nursing students make their career decisions from a combination of personal interests in health care and their desire to help others. From the beginning of the studies students may have strong career preferences. Before they graduate and eventually decide about the future workplace, their career choices undergo several transitions.  Career choices are influenced both by the students inclination before starting medical school as well as any exposure during training in medical school. Experiences in chosen specialties during training as well as the social environment of the medical school, the teaching programme and clinical staff role models can influence career preferences.